EMOTIONAL INTELLIGENCE IN ISLAMIC EDUCATION - Sukria Hairun Nisa; Ika Ramadani; Nabila Aditya (Proceeding International Seminar of Islamic Studies, 2022)
This research is motivated by the problem of emotional intelligence in Islamic education. The purpose of this study is to find out about emotional intelligence in Islamic education and to recognize and overcome difficult situations before they become difficult. This research uses qualitative, descriptive methods and also case studies with observation data collection techniques. In addition, the data is also presented using a descriptive approach in the form of words and writings to clarify the data collected and analyzed. After researching emotional intelligence in Islamic education, namely that emotional intelligence does not only mean being friendly. At certain times it may be necessary not to be friendly, but to be firm in matters that are not by following per under the regulations or unpleasant things to reveal the truth that has been avoided so far. In the context of Islamic education, emotional and spiritual intelligence is the realization of a state of soul and conscience that is clean from diseases such as arrogance, pride, arrogance, revenge, envy, and so on. The way to fill it is through religious education content that is implanted into the souls of students by the teacher. Keywords: Education, EmotionalIntelligence, Islamic